Litigios sociales en torno a la novela de no ficción. Acerca de Recuerdo de la muerte, de Miguel Bonasso - García, Victoria (El Colegio de México, 2021)
Recuerdo de la muerte, by Miguel Bonasso (1984), is recognized as one of the most outstanding expressions of Argentinian non-fiction. The popularity it achieved with its denunciation of the repression suffered during the last military dictatorship contrasts with the intense discussions it aroused during the years after the dictatorship had ended. The present article analyzes these discussions. We aim to show how the dual nature of non-fiction narrative, which attempts to reconcile historical truth with artistic creativity, has conditioned reactions to the publication of Bonasso’s book, for in its reception a major role has been played by social tensions linked to the process of constructing collective memory, truth and justice in the face of State-organized terrorism.